Management Team Incentive: Dispersion and Firm Performance - Bushman, Robert M.; Dai, Zhonglan; Zhang, Weining (The Accounting Review, 2016)
ABSTRACT Recent theory suggests that firms incorporate synergistic interrelationships among executives into optimal incentive design (Edmans, Goldstein, and Zhu 2013). We focus on Pay Performance Sensitivities (PPS) and use dispersion in PPS across top executives as a proxy for the incentive design component shaped by an executive team's synergy profile. We model optimal PPS dispersion and use residuals from this model to measure deviations from optimal. We find that firm performance is increasing (decreasing) in the residual when PPS dispersion is too low (too high). We conjecture that deviations from optimal are sustained by adjustment costs, finding that firms only close around 60 percent of the gap between target and actual PPS dispersion over the subsequent year. Viewing a team's equity grants as a vector, we provide evidence that firms use subsequent equity grants to actively manage PPS dispersion toward optimality. Cross-sectional analysis reveals that the deleterious effect of deviations from optimal is decreasing in the duration of a team's tenure together, and increasing in the importance of effort coordination across team members for firm performance. JEL Classifications: M41.